**Question:**

*True/False?*

\( \lim_{n\to \infty } (n+1)^{1/3} -n^{1/3} = \infty \)

*Hint:*

Simplify the given expression.

**Discussion:**

We feel that \( (n+1)^{1/3} \) goes to infinity at the same speed as \( n^{1/3} \). So in fact, the above limit should be zero.

We make this little bit more rigorous.

\( (n+1)^{1/3} -n^{1/3} = \frac{n+1-n}{(n+1)^{2/3}+(n+1)^{1/3}n^{1/3}+n^{2/3} } \)

\( =\frac{1}{(n+1)^{2/3}+(n+1)^{1/3}n^{1/3}+n^{2/3} } \to 0\) as \(n\to \infty \).

*Related*

## No comments, be the first one to comment !